2021
DOI: 10.3390/d13110548
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a New Filamentous Cyanobacterial Genus, Microcoleusiopsis gen. nov. (Microcoleaceae, Cyanobacteria), from Benthic Mats in Open Channel, Jiangxi Province, China

Abstract: Cyanobacterial taxonomic studies performed by using the modern approaches always lead to creation of many new genera and species. During the field survey for cyanobacterial resources in China, a filamentous cyanobacterial strain was successfully isolated from a microbial mat attached to rock surfaces of the Ganfu Channel, Jiangxi Province, China. This strain was morphologically similar to the cyanobacterial taxa belonging to the genera Microcoleus and Phormidium. The phylogenetic analyses based on 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…2021), Vermifilum D.E.Berthold, Lefler & Laughing-house (Berthold et al . 2021), Microcoleusiopsis R.Geng & G.Yu (Geng et al . 2021), Pseudochroococcus (Duval et al .…”
Section: Resultsmentioning
confidence: 99%
“…2021), Vermifilum D.E.Berthold, Lefler & Laughing-house (Berthold et al . 2021), Microcoleusiopsis R.Geng & G.Yu (Geng et al . 2021), Pseudochroococcus (Duval et al .…”
Section: Resultsmentioning
confidence: 99%
“…The family Aerosakkonemataceae has filamentous trichomes, its apical cells may thicken or have calyptra, its cell length is shorter than the width, and its thylakoids arrangement is generally irregular. A. funiforme, reported by Thu and Watanabe, C. komarekiana reported by da Silva Malone et al, and C. lacustris reported by da Silva Malone et al, all belonging to this family, have gas vacuoles [11][12][13][14][15][16]. Gas vacuoles are intracellular, hollow, cylindrical vesicular protein complexes (such as GvpA or GvpC) that help in the suspension of cyanobacteria [11] and appear to be closely associated with ecological niches, but have also been found in cyanobacteria inhabiting a variety of environments [17].…”
Section: Introductionmentioning
confidence: 79%
“…The family Aerosakkonemataceae has been studied since 2012, and a total of four genera and seven species have been reported to date [10], which include genera Aerosakkonema reported by Thu [9]. It was reported that the genus Aerosakkonema appeared in reservoirs of tropical regions [11]; the genus Cephalothrix appeared in various environments, such as freshwater and alkaline lakes and lake soil shoreline [12,13]; the genus Microseira appeared in freshwater or the rocks of that freshwater in subtropical regions [14,15]; and the genus Potamosiphon appeared in coastal streams [16]. The family Aerosakkonemataceae has filamentous trichomes, its apical cells may thicken or have calyptra, its cell length is shorter than the width, and its thylakoids arrangement is generally irregular.…”
Section: Introductionmentioning
confidence: 99%
“…(2013), Limnospira Nowicka‐Krawczyk, Mühlsteinová & Hauer (2019), Microcoleus Desmazières ex Gomont (Gomont 1892a), Microcoleusiopsis R. Geng et G. Yu (Geng et al . 2021), Neolyngbya T.A. Caires, C.L.…”
Section: Methodsmentioning
confidence: 99%